Effect of nano-α-Al2O3 Particles on Mechanical Properties of Glass-Fibre Reinforced Epoxy Hybrid Composites - Anil Kumar Veerapaneni; Chandrasekar Kuppan; Murthy Chavali (ASEAN Journal of Chemical Engineering, 2021)
The present work deals with the mechanical properties of hybrid nanocomposites made of epoxy/glass fibre dispersed with different weight percentages of nano-α-Al2O3 powder . The nanoparticles were synthesized by a high energy ball milling technique (60 and 200 nm).. The effect of nano-α-Al2O3 size and content (wt%) on mechanical properties, such as tensile, flexural, interlaminar shear stress (ILSS) and hardness was investigated. The addition of nano-α-Al2O3 enhanced all measured mechanical parameters because of their higher surface area and interfacial polymer-metal interaction. The nanoparticle-embedded laminates showed an improvement in flexural strength and hardness compared to laminate without nano-α-Al2O3. Among all the wt% of varied sizes of nano-α-Al2O3, the highest tensile strength was shown by the addition of 0.5 wt% 200nm nano-α-Al2O3 (167.80 N/m2). The highest flexural strength (378.39 N/m2) Vickers hardness (86.72) were observed for laminates containing 1.5 wt% of 60nm nano-α-Al2O3, while the highest ILSS (31.21 Ksi) was observed for 0.5 wt% of 60nm nano-α-Al2O3. This study showed that there was a higher interaction between the nanoparticle and polymer resin, which led to increasing the mechanical properties of the laminate. This finding show that diversifiying the application of these hybrid materials was possible by adding nano-alumina.